2018
DOI: 10.1007/s41887-018-0023-5
|View full text |Cite
|
Sign up to set email alerts
|

Sorry, Wrong Number: Tracking Court Attendance Targeting Through Testing a “Nudge” Text

Abstract: Research Question Will sending defendants text messages reminding them that they are due at court, the day before, cause more defendants to attend the first scheduled Magistrate's Court hearing? Data The study universe included all 946 defendants in Hampshire and the Isle of Wight sent a postal requisition requiring them to attend court, who also had a mobile phone number, between January and June 2017. Two outcomes were then tracked: court attendance and fail-to-appear warrants. Method The experiment randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…However, in studies that found weaker effects (e.g., Bornstein et al, 2013 andLowenkamp et al, 2018), 34 or 67 people must be given reminders to prevent one person from failing to appear. Notably, the relative risk F I G U R E 2 Forrest plot for odds of failure to appear reduction, absolute risk reduction, and number needed to treat reported for the study by Chivers and Barnes (2018) are all negative because this study found that the group of people who were sent reminders had more failures to appear. We also calculated the summated relative and absolute risk reductions and the summated number needed to treat using the total rate of failures to appear across all 12 treatment groups (17.4%) and all control/comparison groups (25.1%).…”
Section: Study and Sample Characteristicsmentioning
confidence: 91%
See 2 more Smart Citations
“…However, in studies that found weaker effects (e.g., Bornstein et al, 2013 andLowenkamp et al, 2018), 34 or 67 people must be given reminders to prevent one person from failing to appear. Notably, the relative risk F I G U R E 2 Forrest plot for odds of failure to appear reduction, absolute risk reduction, and number needed to treat reported for the study by Chivers and Barnes (2018) are all negative because this study found that the group of people who were sent reminders had more failures to appear. We also calculated the summated relative and absolute risk reductions and the summated number needed to treat using the total rate of failures to appear across all 12 treatment groups (17.4%) and all control/comparison groups (25.1%).…”
Section: Study and Sample Characteristicsmentioning
confidence: 91%
“…All studies compared groups of people who received reminders to groups who did not on subsequent rates of failure to appear in court. Some studies found that reminders did reduce failures to appear (Bornstein et al, 2013;Fishbane et al, 2020;Howat et al, 2016) and other studies found that they did not (Chivers & Barnes, 2018;Lowenkamp et al, 2018). Despite the mixed findings of individual studies, two recent qualitative reviews-one of 13 court reminder programs (Thomas & Ahmed, 2021) and the other of pretrial support programs including but not limited to court reminders (Hatton & Smith, 2020)-generally conclude that reminders are effective.…”
Section: Court Date Remindersmentioning
confidence: 99%
See 1 more Smart Citation
“…The redesigned form reduced failure to attend by 13%, which translated to preventing around 17,000 warrants being issued in the New York City area. The results of this study are at odds with those of Chivers and Barnes (2018). In this trial, a treatment group of 474 defendants in the Hampshire and the Isle of Wight (UK) were sent a text message the day before their court appearance, whilst the control group (n = 472) received the standard postal notification.…”
Section: Introductionmentioning
confidence: 88%
“…One widely discussed innovation from the "nudge" literature (Thaler & Sunstein, 2008) includes sending text messages to remind individuals to attend court appearances and other important scheduled events. One randomized trial of this approach by a police agency with arrested persons scheduled for court (Chivers & Barnes, 2018) in England found no effect on attendance-due to police failing to secure correct phone numbers at point of arrest. Another randomized trial in England with victims and witnesses tested text reminders 2-3 days prior to court dates, with no discernible effect on attendance rates (Cumberbatch & Barnes, 2018).…”
Section: Introductionmentioning
confidence: 99%